(untitled) (Journal of the College of Basic Education, 2022)
The aim of the current research is to identify the effect of integrating thinking skills within the cognitive content on the achievement of biology subject among fourth grade female students, and in order to verify this, the two researchers formulated the following zero hypothesis: